PENINGKATAN KEMAMPUAN TEKNIK DASAR LEMPAR CAKRAM MELALUI METODE DEMONSTRASI - Made Armade (STKIP ROKANIA, 2017)
This classroom action research aims to improve the basic technique of throwing discs, such as the placement of the disc grip of the hand, the positioning of the body when throwing discs, how to swing discs and the way foot repulsion while releasing the disc. This research method is descriptive qualitative. The samples were all students of SMP YLPI P.Marpoyan Kota Pekanbaru consisting of 24 students consisting of 12 males and12 females. Classroom Action Research is conducted in two cycles. The research instrument used is activity sheet of learners. Result of research indicate that there is improvement of basic technique ability throw disc students of class VIIIa SMP YLPI P. Marpoyan city Pekanbaru through method of demonstration.